Implementasi Teknik Konseling Behavioral dalam Mengurangi Stres pada Siswa yang Terpapar Cyberbullying - muhammad ilham; Muhammad Bahrul Ulum Mubarok (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Cyberbullying has become an increasingly concerning social phenomenon in the digital age, with serious psychological impacts such as stress, anxiety, and depression on students. This study aims to implement behavioral counseling techniques as a practical solution to reduce stress among students exposed to cyberbullying. Behavioral counseling is chosen for its ability to help individuals transform negative thought patterns and behaviors into more adaptive ones, thereby managing stress more effectively. This research uses a qualitative approach with a case study design, allowing for an in-depth exploration of students' emotional experiences and the effectiveness of behavioral counseling techniques. Data were collected through in-depth interviews, participatory observation, and document analysis, with primary respondents being students who experienced cyberbullying and supporting informants such as school counselors, peers, and parents. Data analysis was conducted through data reduction, data display, and data verification to ensure the validity and reliability of the findings. The results of this study are expected to provide practical recommendations for schools in implementing behavioral counseling techniques to create a safe and supportive environment for students. Keywords: Behavioral Counseling; Cyberbullying